Africa development indicators 2006 (The World Bank, 2006)
"African Development Indicators 2006" provides the most detailed collection of data on Africa available in one volume. It contains more than 500 macroeconomic, sectoral, and social indicators, covering some 50 African countries with data from 1970-2004. The book is grouped into 15 chapters: background data; national accounts; prices and exchange rates; money and banking; external sector; external debt and related flows; government finance; agriculture; power, communications, and transportation; public enterprises; labor force and employment; aid flows; social indicators; environmental indicators; and HIPC debt initiative.